2007
DOI: 10.1111/j.1740-0929.2007.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urea treatment of potato pulp and inclusion levels of potato pulp silage in supplements on digestibility and ruminal fermentation in beef steers

Abstract: Six Wagyu (Japanese Black) steers fitted with a ruminal cannula were used in a split‐plot design experiment comprising a 3 × 3 Latin square design (whole plot) and a randomized blocks design (subplot) to determine the effect of the treatment of potato pulp (PP) with urea and the effect of inclusion levels of PP silage in feed supplement on digestibility, ruminal in situ degradation and ruminal fermentation. The whole plot consisted of 20%, 50% and 80% PP silage (dry matter (DM) basis), with PP silage replacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 18 publications
11
12
0
Order By: Relevance
“…Increasing the levels of potato pulp silage in concentrate and roughage sources did not significantly affect feed intake in cows, although the values of total DM and TDN intake declined from 2272.8 to 2080.0 kg and from 1712.4 to 1532.8 kg as the levels of potato pulp silage in concentrate increased. These results are in agreement with the findings of Sugimoto et al. (2007a), who observed no significant effects of different inclusion levels of potato pulp silage in supplements on feed intake in steers.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Increasing the levels of potato pulp silage in concentrate and roughage sources did not significantly affect feed intake in cows, although the values of total DM and TDN intake declined from 2272.8 to 2080.0 kg and from 1712.4 to 1532.8 kg as the levels of potato pulp silage in concentrate increased. These results are in agreement with the findings of Sugimoto et al. (2007a), who observed no significant effects of different inclusion levels of potato pulp silage in supplements on feed intake in steers.…”
Section: Resultssupporting
confidence: 93%
“…Steers fed potato pulp silage will require additional protein because potato pulp has a low protein content (Brugman & Dickey 1961). Sugimoto et al (2007a) described that the treatment of potato pulp with urea can improve the nitrogen supply to rumen microbes as a non-protein nitrogen source and facilitate microbial access to starch contained in residual intact cells of potato pulp silage in the rumen. However, little is known about the fattening performance and carcass quality with substitution of urea-treated potato pulp silage for concentrate.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of PP, which has a low protein, with urea can improve the nitrogen supply to rumen microbes (Sugimoto et al. 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Sugimoto et al. (2007a) observed that fluctuation in ruminal NH 3 ‐N was larger when steers were fed the urea‐treated PP silage than that when they were fed the untreated PP silage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation